Effect of Electronegativity and Covalent Radius of Halide Ions on Adsorption on Lead in Acid Medium - H. Wahdan, Mostafa; K. Gomma, Gamal (Asian Journal of Chemistry, 2010)
The corrosion rate of lead in 0.1 M chloroacetic acids with and without different additives of Cl, Br and I has been calculated gravimetrically and potentiokinetically. The results indicate that halide ions adsorbed on the electrode surface inhibit the dissolution reaction. Asorption occurs according to Langmuir isotherm. The inhibition effect increases in the order I– > Br– > Cl–, which seems to indicate that radii and electronegativity of halogens play an important role.